PENERAPAN METODE LOGIKA FUZZY MODEL TAHANI DALAM PEMILIHAN HARDWARE KOMPUTER - SETIAWAN, MOH. HERI; GANDHIADI, G.K.; HARINI, LUH PUTU IDA (E-Jurnal Matematika, 2017)
This study to determine the selection of computer hardware using fuzzy database method. This is because of many series of hardware produced by the manufacture, so the public will be confused in determining the choice of a combination of computer assembly. In this study the processor, motherboard, random access memory, hard disk, vga cards, power supply studied to find best recommendation. The result obtained from this study these several results obtained in study in the form of recommendation, that is if the recommendation value 0 then the hardware is not displayed as a decision, whereas if the recommendation value is greater than 0 and less than or equal to 1 the device will be displayed as a decision according to the value of its recommendation .